Numerical estimation and arithmetic performance - Mariana Lima Duro; Beatriz Vargas Dorneles (Amazônia, 2020)
The present study correlated the accuracy of the number estimation in two number estimation tests: the Numerosity Test (TENQ) and the Number Line Estimation Test (TERN), with the performance in a standardized arithmetic test (TDE), in students of the 5th-6th grade of public and private school in Porto Alegre / RS. The main objective of this study was to verify if the performance in different tasks of numer estimation is related to the arithmetic performance of these students. The data indicate that the arithmetic performance presented a moderate to strong correlation with the performance in estimation in both tasks when considering the 0-100 numerical interval. This result indicated that arithmetical knowledge may be related, in some way, to the estimative ability.